The role of the school library: resource center in the current educational environment - Lowrie, Jean (1980)
The school library is an important instrument in the education of the children, for this reason these centers have evolved completely resting on many aspects the educational programs, to such a point of turning into an exciting center of resources with collection of materials, equipment in many formats and with a professionals' body working narrowly inside a school system.